Associations of Electromyographic Activity of Anterior Temporalis Muscles, Sex, and Occlusal Classes in Asymptomatic Young Adults - Wieczorek, Aneta; Czarnek, Marcin; Loster, Jolanta E (Journal of Dentistry Indonesia, 2021)
Symmetry evaluation of the craniofacial complex generally involves models of mandibular movement and masticatory muscle activity, especially during the growth of the craniofacial complex. Objectives: The aim of the study was to determine what, if any, associations exist between the activity of the masticatory muscles, sex, and occlusal classes in asymptomatic young adults. Methods:18-year-old volunteers, showing no symptoms of TMD based on an RDC/TMD examination, were included in the study.Surface electromyography (sEMG) recording was used to quantify the activity of masticatory muscles. The occlusal contact points were analyzed using a T-scan III Evolution 7.01 device. Occlusal classes were graded, employing an approach based on plaster study models. Results: In Class I–II subjects, we found significant differences only in the voltage of LTA in correlation with the gender and occlusal Class. Conclusions: Our findings show that the electromyography voltage of LTA significantly differs according to sex and occlusal Class. The voltage is higher in the female occlusal class II group, while the voltage is less in the male Class I and II group. This may be responsible for the symmetry index, which shows the predominance of the right-side muscles in all gender and occlusal groups.